Pretreatment of Sludge Palm Oil (SPO) for biodiesel production by esterification - Hayyan, Adeeb; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Mohd Hakimi, Noor Irma Nazashida; Mohd Siran, Yosri; Tahiruddin, Shawaluddin (2008)
Biodiesel is receiving an increased attention because of increases in crude oil prices, limited resources of fossil oil and environmental concerns. There has been renewed focus on using vegetable oils and animal fats to make biodiesel fuels. The main challenges in biodiesel industry are its production cost and limited availability of fats and oils resources. There are two aspects of the production cost of biodiesel, the costs of raw material and the cost of processing. The cost of raw materials accounts for 60 to 70% of the total cost of biodiesel production. However, there are large amounts of low grade oils from palm oil industry that could be converted to biodiesel such as sludge palm oil (SPO). SPO is a by-product of the palm oil milling process that contains high free fatty acids (FFA). The use of SPO can lower the cost of biodiesel production significantly. The problem in processing SPO to biodiesel is the high free fatty acid content in the oil restricts the conversion to biodiesel when using conventional transesterification process. This invention develops a process to treat the SPO and produce biodiesel within the standard specifications of biodieselfuel.